Effect of Fertilizer and Fertilizer Manure Nickerson Star Swallow on Growth Seeds Rubber (Havea brasiliensis Muell Arg) Origin Grafting: Pengaruh Pemberian Pupuk Nickerson Star dan Pupuk Kotoran Burung Walet Terhadap Pertumbuhan Bibit Tanaman Karet (Havea brasiliensis Muell Arg) Asal Okulasi - Jarkani; Akhmad Sopian; Mahdalena (Agrifarm : Jurnal Ilmu Pertanian, 2015)
Effect of Organic Fertilizer and Fertilizer Manure Nickerson Star Swallow on Growth Seeds Rubber (Hevea brasiliensis Muell Arg.) Origin grafting. The purpose of research to determine the effect of fertilizer and manure Nickerson star swiftlets to growth rubber seedlings (Hevea brasiliensis Muell Arg.) From grafting. This research was carried out for 4 (four) months, from May to August 2012. The study was conducted in the village of Loa Kulu Margasari District of Kutai Regency Village Jembayan Kertanegara East Kalimantan. Research arranged in a randomized block design with 3 x 4 factorial analysis and repeated 3 times. The first factor is the provision of Nickerson star fertilizer (N) which consists of three levels, namely: N0 (control), N1 (200 g / polybag), N2 (400 g / polybag). The second factor is the provision of manure swiftlet (W) which consists of 4 levels, namely: W0 (control), W1 (200 g / polybag), W2 (250 g / polybag), W3 (300 g / polybag). The results showed organic fertilizer Nickerson star treatment had no significant effect on all parameters plant height, stem diameter, number of leaves and number of umbrella, while the birds' manure very significant effect on the best treatment W1 (200 g / polybag). This is because the manure is very rich in elements swallow total N and organic C coupled with a high pH so as to spur the growth of rubber seedlings and efficiency in the use of land.